Reliability Analysis for the Gear Fracture based on Energy Release Rate Criterion - Song Ping; Song Feifei (Jixie chuandong)
Based on energy release rate criterion,a reliability analysis model is presented for the gear fracture. Firstly,the formula of gear fracture energy release rate is deduced,then the material parameter,crack size,load which affecting on gear fracture are regarded as random variables. The performance function of the crack structure failure is built by taking advantage of the energy release rate criterion. The first- order second-moment method and stochastic finite element method are used to calculate the reliability. The computation results show that this suggested method has advantages of high accuracy and efficiency.